1998
DOI: 10.1046/j.1469-7580.1998.19240595.x
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic study of the renal glomerulus by an in vivo cryotechnique combined with freeze‐substitution

Abstract: The 3-dimensional ultrastructure of mouse renal glomeruli under normal haemodynamic conditions was studied by scanning electron microscopy using an in vivo cryotechnique followed by freeze-substitution, and compared with glomeruli prepared by conventional fixation methods. Mouse kidneys were frozen with a cryoknife apparatus and a liquid isopentane-propane mixture (k193 mC). Surface areas of the frozen tissues were freeze-fractured with a scalpel in liquid nitrogen. The specimens were routinely freeze-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Dehydration in an organic solvent at ambient temperature may cause shrinkage (Boyde 1980); however, this effect can be reduced by the use of t-butyl alcohol (Yu et al 1998). We found that freeze substitution in methanol preserved the fine structure of the cell after maceration more effectively.…”
Section: Discussionmentioning
confidence: 72%
“…Dehydration in an organic solvent at ambient temperature may cause shrinkage (Boyde 1980); however, this effect can be reduced by the use of t-butyl alcohol (Yu et al 1998). We found that freeze substitution in methanol preserved the fine structure of the cell after maceration more effectively.…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, our in vivo cryotechnique was applied to the IHC analysis of pCREB in the mouse cerebellum. It has been well known that both ultrastructure and molecular distribution could be easily changed by stopping the blood supply, probably due to anoxia and rapid loss of blood volume and pressure (Ohno et al 1996(Ohno et al ,2001Terada et al 1998;Xue et al 1998;Yu et al 1998;Takayama et al 2000;Watanabe et al 2000). In addition, such loss of blood supply to organs, which was inevitable with conven- ( a-d,f,g,i,j ) and DAPI ( e,g,h j ) with ( b,d,h-j ) or without ( a,c,e-g ) microwave irradiation in serial sections of paraffin-embedded tissues prepared by conventional fixation-dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…This is because ultimately prompt immobilization of molecules and structures, which is known to be most characteristic of the cryotechniques (CrT), can be hardly achieved by any kinds of routine chemical fixation steps. Recently, our "in vivo cryotechnique" followed by the freeze-substitution (FS) has been developed to overcome problematic ultrastructural changes of cells and tissues caused by cessation of blood circulation and resection of animal organs (Ohno et al 1996(Ohno et al ,2001Terada et al 1998;Xue et al 1998;Yu et al 1998;Takayama et al 1999Takayama et al ,2000Watanabe et al 2000;Zea-Aragon et al 2004a,b). Therefore, some ultrastructural and immunoreactive problems might be improved to a considerable degree at the electron microscopic level by using the in vivo cryotechnique.…”
mentioning
confidence: 99%
“…Flowing erythrocytes in blood vessels can easily change their shape because of the surrounding conditions, such as the types of vessels or flow speed, as well as some processes for preparing electron microscopic specimens (Terada et al, 1998a). Using the ''in vivo cryotechnique,'' we already reported three-dimensional shapes of flowing erythrocytes in sinusoids of living mouse livers (Terada et al, 1998b) and spleens (Xue et al, 2001), large blood vessels, including the aorta and caudal vena cava (Xue et al, 1998), glomerular capillaries of mouse kidneys (Yu et al, 1998), and capillaries of mouse lungs (Takayama et al, 2000). A shear stress from the flow is one of the factors, which affect the erythrocyte shapes (Fisher et al, 1978).…”
Section: Introductionmentioning
confidence: 96%